Alteraciones morfológicas inducidas por ampicilina en Campylobacter - Hernández, Francisco; Rivera, Patricia; Herrera, Merco Luis; Rodríguez, Rosa María (Revista de Biología Tropical, 1986)
Morphologic changes in Campylobacter fetus ssp. jejuni were evaluated as cultivated on thioglycollute broth, containing minimum of 0.1, 1,3 and 10 Ampiciline minimal inhibitory concentration (MIC). During the first four hours of incubation, no changes occured in the presence of 0.1 MIC; but with the rest of the ampiciline dosis, even at the first hour, a proportion larger than 5% of filament-policurved forms was found, and it increased with the incubation time. The greatest number of altered bacteria was found with the u se of 10 MIC. No other morphologic changes were observed.